Pelatihan Pengenalan dan Penanganan Tanda- Tanda Bahaya Kehamilan pada Ibu Hamil dan Keluarga dalam Upaya Menurunkan Kasus Kematian Ibu di Puskesmas Bebesen Kabupaten Aceh Tengah - Lisni Lisni; Hasritawati Hasritawati; Sri Wahyuni (Compromise Journal Community Proffesional Service Journal, 2024)
The main cause of maternal mortality is bleeding (28%), as well as SDKI 2012 data shows that the highest cause of maternal mortality is bleeding (42%). This is due to three delays that occur, namely being late in recognizing the danger signs and making decisions; late arrival at health facilities; and late in getting services at health facilities. These three delays can be prevented by providing knowledge and understanding to pregnant women about danger signs in childbirth, if you experience immediately coming to the health center or health workers so that delays can be prevented, you immediately get help which can ultimately reduce the case of your death. The purpose of the activity is to increase the understanding and ability of pregnant women to recognize the danger signs of pregnancy early, immediately seek help so that mothers and babies are safe and have an impact on decreasing the Maternal Mortality Rate. The service method used in its implementation is the stage of preparation, implementation, monitoring and evaluation of activities. The results of the activity were obtained to increase the knowledge of mothers and families about the danger signs in pregnancy, early detection of prevention and early actions that must be taken/handled to prevent maternal and child deaths.